Decolonizing the school curriculum for equity and social justice in South Africa - Lebeloane, L. (Koers, 2017)
The starting point of decolonizing the curriculum is in the schools and classrooms that I regard as the formal education laboratories for equity and social justice in a just society. Unfortunately, many South African public schools' curriculum are not yet decolonized and thus continue to perpetuate the preparation of learners for leading western lives in a continent that is not western by nature. The South African school curriculum does little to address decolonization for equity and social justice in the South African public schools.This article argues for the decolonization of public school curriculum for equity and social justice in South Africa. Background information is provided. Key terms will be decoded, followed by an outline of the frame of reference, method of research and a discussion of the process of decolonising the curriculum. The importance of decolonizing the school curriculum for equity and social justice in South Africa will be discussed. Threats of not decolonizing the curriculum for equity and social justice in South Africa will also be discussed. Conclusions will be drawn.